Sex and the city: geographies of prostitution in the urban West - Hubbard, Phil (Ashgate, 1999)
Klappentext: Prostitution has always played a crucial symbolic role in the definition of moral and sexual standards and, as such, the figure of the prostitute has been paradigmatic in the history of the sex and the city. Focusing on the geographies of female prostitution in Western societies, this book explores the nature of sites of sex work and the ways they shape the lives of prostitutes (and their clients). In so doing, the book aims not simply to present a static "mapping" of sex work, but seeks to highlight how these public and private ssites are struggled over, with prostitutes often resisting the strategies of social and legal control designed to regulate their working practices. The book consequently engages with a number of contemporary debates in social, cultural and gender geography surrounding the importance of public and private spaces in producing (and reproducing) gender, sex and bodily identities.